An acute complicated pancreatitis: principles of surgical tactics, using miniinvasive technologies and standard operations - V. P. Andriushchenko; O. T. Girniak; D. V. Andriushchenko (Клінічна хірургія)
Objective. To elaborate a surgical tactics for patients, suffering  an acute complicated pancreatitis (ACP), using miniinvasive technologies (МІТ) and standard surgical interventions.